Arab voices : what they are saying to us, and why it matters - Zogby, James J. (New York : Palgrave Macmillan, 2010)
"The co-founder of the renowned polling firm Zogby International draws from 40 years of the most extensive polls from the Arab World to lift the fog that has obscured this culture for centuries"--Provided by publisher.
Includes bibliographical references ( p. [215]-219) and index.
Keywords: Arabs -- Attitudes; Public opinion -- Arab Countries; National characteristics, Arab; United States -- Foreign public opinion, Arab